Solidarność Dolnośląska . pismo organizacji "Solidarność Walcząca", no. 16, 1986 - Kędra, Dariusz; Stando, Wojciech; Galecki, Włodzimierz; Rozpędowski, Radosław; Świat, Jacek (AISW, 1986)
Creation and circulation: Publication suspended between 23.07.1988 and 18.06.1989 due to changes in the editorial board. From issue no. 74(1990) published legally